2020
DOI: 10.1186/s13000-020-0925-y
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous pilomatrical carcinosarcoma: a case report with molecular analysis and literature review

Abstract: Background: Cutaneous pilomatrical carcinosarcoma (CS) is a very rare biphasic tumor composed of admixed epithelial and mesenchymal malignant cells, with limited information on its pathogenesis. We report a case of pilomatrical CS of the scalp with comparative immunohistochemical and molecular analysis together with a review of the literature. Case presentation: A 74-year-old woman presented with a rapidly growing long-standing tumor of the scalp. The tumor was surgically resected. Histologically, the tumor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…WNT activation leads to downregulation of E‐cadherin expression, which causes the migration of β‐catenin to the nucleus. This phenomenon of EMT is characterized by a loss of E‐cadherin membranous expression in the sarcomatous component and an acquisition of abnormal cytoplasmic and/or nuclear expression of β‐catenin 11,12 . In our case, the sarcomatous component demonstrated a complete loss of E‐cadherin expression.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…WNT activation leads to downregulation of E‐cadherin expression, which causes the migration of β‐catenin to the nucleus. This phenomenon of EMT is characterized by a loss of E‐cadherin membranous expression in the sarcomatous component and an acquisition of abnormal cytoplasmic and/or nuclear expression of β‐catenin 11,12 . In our case, the sarcomatous component demonstrated a complete loss of E‐cadherin expression.…”
Section: Discussionmentioning
confidence: 54%
“…This phenomenon of EMT is characterized by a loss of Ecadherin membranous expression in the sarcomatous component and an acquisition of abnormal cytoplasmic and/or nuclear expression of β-catenin. 11,12 In our case, the sarcomatous component demonstrated a complete loss of E-cadherin expression. However, neither nuclear nor cytoplasmic β-catenin expression was observed.…”
Section: Case Reportmentioning
confidence: 51%
“…This suggested that CpG methylation changes may be induced by oncogenic beta-catenin, where beta-catenin was found to have interacted with DNA methyltransferase I in a mutually stabilizing interaction in the nuclei of cancer cells [ 49 ]. Although, majority of CDKN2A mutations are inactivating mutations (i.e., loss-of-function mutations), an interesting study found an increased copy number of CDKN2A gene in a nonsyndromic case with cutaneous pilomatrical carcinosarcoma but mutation of exon 3 of the CTNNB1 gene was not detected in that case [ 50 ]. For the other genes on the short arm of chromosome 9, there were no evidences that link them to pathogenesis of pilomatricoma.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors are known for their biphasic nature, rapid rate of growth, ulceration, and exophytic-appearance that can be misleading to even the most-experienced clinicians. Several histologic forms of carcinosarcoma of the skin have been described, including basal cell, squamous cell, pilomatrical, and trichoblastic carcinosarcoma [ 10 - 12 ]. As opposed to adnexally derived carcinosarcomas, epidermally derived carcinosarcomas are reported to have a better five-year survival rates, with disease-free survival of 70% compared to 25%, respectively [ 6 ].…”
Section: Discussionmentioning
confidence: 99%